Essential but Ill-Prepared: How the COVID-19 Pandemic Affects the Mental Health of the Grocery Store Workforce. (January 2022) - Mayer, Brian; Arora, Mona; Helm, Sabrina; Barnett, Melissa
Objectives: Frontline essential workers face elevated risks of exposure to COVID-19 because of the interactive nature of their jobs, which require high levels of interaction with the general public and coworkers. The impact of these elevated risks on the mental health of essential workers, especially outside the health care sector, is not well studied. To address this knowledge gap, we examined correlations between perceptions of workplace risks and mental health distress among grocery store workers in Arizona. Methods: We collected the first statewide sample of essential workers outside the health care sector focused on mental health and well-being. A total of 3344 grocery store workers in Arizona completed an online survey in July 2020. We used multiple regression models to identify demographic and work-based correlates of mental health distress. Results: Levels of mental health distress among respondents were high: 557 of 3169 (17.6%) reported severe levels and 482 of 3168 (15.2%) reported moderate levels. Perceptions of workplace safety were strongly correlated with significantly reduced levels of mental health distress (ß = −1.44; SE = 0.20) and reduced perceived stress (ß = −0.97; SE = 0.16). Financially disadvantaged workers and employees aged <55 reported high levels of mental health distress. Perceptions of safety and protection in the workplace were significantly correlated with availability of safety trainings, social distancing, and policies governing customer behaviors. Conclusions: Lacking sufficient workplace protections, grocery store employees in Arizona experienced high levels of mental health distress during the COVID-19 pandemic. Providing clear federal and state policies to employers to guide implementation of workplace protections may help reduce sources of mental health distress.